The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6cp01561a
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen–iron interaction in liquid lead–bismuth eutectic alloy

Abstract: Iron released by steel corrosion was found to be a key impurity in reactions with dissolved oxygen in liquid lead-bismuth eutectic alloys. The iron-oxygen-magnetite equilibrium was characterized, allowing the quantification of phenomena that are important for long-term operation of lead-alloy based installations such as corrosion rate control and management of precipitates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Heterogeneous nucleation in LBE is considered possible because of the relatively large number of impurity particles present in the LBE under the conditions tested. Solid oxides, such as magnetite, 24 can be present in LBE in contact with stainless steel surfaces. The results presented here show comparable values of oversaturation independent of the LBE residence time in the experimental setups, suggesting the absence of dependency on corrosion product impurity content.…”
mentioning
confidence: 99%
“…Heterogeneous nucleation in LBE is considered possible because of the relatively large number of impurity particles present in the LBE under the conditions tested. Solid oxides, such as magnetite, 24 can be present in LBE in contact with stainless steel surfaces. The results presented here show comparable values of oversaturation independent of the LBE residence time in the experimental setups, suggesting the absence of dependency on corrosion product impurity content.…”
mentioning
confidence: 99%
“…where solids and dissolved species are indicated by (s) and (lbe), respectively. This reaction was also found to have a strong impact on the local oxygen concentration and precipitate formation in larger LBE installations such as the CRAFT corrosion loop [15]. Large differences of the oxygen concentration between the hot leg, where the oxygen control point was located, and the cold leg were observed under certain conditions.…”
Section: Impurity Chemistry and Managementmentioning
confidence: 87%
“…One of the abundant corrosion products expected to be released in the LBE of MYRRHA is iron. The reaction between dissolved iron, and dissolved oxygen in liquid LBE has been characterized [15]. It was found that many experimental observations, such as the change of dissolved oxygen concentration during temperature changes in a system with constant composition, can be described by the simple equilibrium:…”
Section: Impurity Chemistry and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, SCK-CEN has investigated the saturation concentration of Fe in LBE of different oxygen concentration [13] and the relation is given by Eq. (3)…”
Section: Corrosion Products Concentration Distributionmentioning
confidence: 99%